PENERAPAN PROBLEM BASED LEARNING (PBL) BERBANTUAN LIVEWORKSHEET UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X SMAN BALUNG JEMBER PADA MATERI PELUANG - Ahmad Aji; Abdul Halim Fathani (Institut Pendidikan Tapanuli Selatan, 2024)
This research aims to determine whether the use of the Problem-Based Learning (PBL) model and Liveworksheet media can improve mathematics learning outcomes in class X.8 of SMAN Balung Jember. This research is classroom action research with research instruments namely interview sheets, observation sheets, and learning outcome measurement sheets. The data analysis technique used is quantitative data in the form of numbers and quantitative descriptive in the form of an explanation of the results of the numbers. Then it is explained in a comparative descriptive manner, namely comparing the test scores before the pre-cycle with the inter-cycle scores after the action was given. This research increased from pre-cycle, cycle I, cycle II, and cycle III, namely 64%. The results can be concluded that by using the PBL model for learning opportunities, the learning outcomes of class X.8 students at SMAN Balung Jember can be improved.